A Fast and Easy-To-Go Method for the Preparation of Au Nanocluster and Its Application for Fe(III) Cation Sensing - Zhu, Peibin; Chen, Wen; Liu, Liang (Frontiers in Chemistry, 2021)
In this paper, we reported the synthesis and characterization of gold nanoclusters (AuNCs) with diameter of ~ 2 nm. A simple method of microwave-assisted reaction was applied here, with L-Cysteine as both reducing agent and stabilizer. The resulting AuNCs were analyzed by means of TEM, XPS, DLS and IR. Their photophysical performance was then analyzed in detail, including UV-Vis absorption, emission, quantum yield and lifetime. Efficient red emission was observed from these AuNCs, originating from ligand to metal nanoparticle core charge transfer (LMNCT). This red emission was found quenchable by Fe(III) cation. Corresponding quenching curve and sensing performance were discussed. An effective working region of 0-80 μM with LOD of 3.9 μM was finally observed. Their quenching mechanism was revealed as Fe(III) energy competing for LMNCT process. The novelty and advancement of this work is the simple synthesis and impressive sensing performance, including wide working region, good linearity and selectivity.